Petromineralogy and hydrothermal alteration of the Limoncillo Vein South of Morro Solar, Lima, Peru - Baldoceda Dionisio, Ánghelo Aníbal (2020)
This research work consists of petromineralogical analysis and infrared spectrometry to determine mineralization and hydrothermal alterations in the Limoncillo vein. This structure is located in the quartz-arenites of the Marcavilca Member of the Morro Solar in Lima and is associated with a dike and a sinestral fault of N-S direction. The mineral of economic interest is represented by native gold scattered on the hydrothermal quartz of the vein and, in greater concentration, on the quartz arenites adjacent to the Limoncillo Vein. Using infrared spectrometry it was possible to determine two types of hydrothermal alteration: 1) Argillic alteration represented by the mineralogical association of kaolinite, illite-smectite and potassium illite, which suggest a formation temperature between 150 ° and 200 ° C and a pH moderately acid, with a tendency to neutralize; and 2) sub-propylitic alteration evidenced only by the Chabasite mineral species, which is typical of temperatures between 100 ° and 150 ° C and a neutral to alkaline pH. Finally, the association of alteration minerals reflects a variation on the pH fluid (which is moderately acidic to neutral-alkaline), and allow define the temperature range of 200°C to 61°C, which indicates that the Limoncillo vein would be part of a system of epithermal veins.